Pengembangan Modul Interaktif Berbasis Augmented Reality Pada Materi Bangun Ruang Kelas V Sekolah Dasar - Rifa’atul Mahmudah; Musabihatul Kudsiah; Zulfikar Ahmadi; Rohini, Rohini (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to develop interactive modules based on augmented reality on grade 5 building materials as a teaching tool in delivering lesson materials and supporting the learning process carried out at SDN 2 Kelayu Selatan in the 2022/2023 school year. This research is a research and development (Research and Development) using the ADDIE development model which consists of 5 steps, namely (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. This study was conducted on grade 5 students with a total of 11 students. This research and development instrument uses validation sheets and student response questionnaires. The results of the media expert validation test with a total score of 94 are in the range of X > 79.68 scores in the